The comparison of reading interests of public and private high school students in Tagaytay City and Silang, Cavite - Paras, Bernice B.; Gonzales, Grace Marie B.; Faderon, Rosalie B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
The study identified, analyzed and compared the reading interests of 541 high school students from four diverse private and public schools in Tagaytay City and Silang, Cavite. Respondents were from Tagaytay City Science National High School and General Vito Belarmino National High School, Kalubkob, Silang, Cavite (public schools) and Adventist University of the Philippines Academy, Puting Kahoy, Silang, Cavite and Cavite Institute, Iba, Silang, Cavite (private schools). Majority of the respondents or 86 percent were aged 13 to 16 years old. Of the 541 who participated, (383 or 71 percent) were female.
Forty six of the respondents were third and fourth year students. Three hundred thirty one of the respondents were students from public schools. TCSNHS had 174 students who participated while 157 came from GVBNHS. CI had (125 or 23 percent) while AUPA had the least, with (85 or 16 percent). The major findings of the study were: 1) Majority of the students in the private schools owned more books than those in the public schools. But though 67 percent of the public school students had fewer books in their home, they read as often and devoted the same amount of time to reading. Majority of these read no more than ten books a week and spent less than four hours a week in reading. Of these books owned by students, 69 percent of the students in public schools read only 10 hours per week compared to 53 percent of the students in private school. With the exception of GVBNHS students who prefer to read books and other reading materials in Tagalog at 45 most of the students prefer to read their materials in English with 70 percent of TCSNHS school students and 78 percent of the private school students. From the result of the survey, the study shows that reading interest and preferences between public and private high school students have no substantial dissimilarity.
As a result of the study, the following recommendations were made: 1)The secondary school administrators and librarians should make every effort to upgrade their libraries so that the students have a decent place to study and loan books that will motivate them to read more. They should also develop new or up-to-date programs on how to encourage reading among students; 2) Secondary students must know fully that "Reading is one of the most effective ways to acquire knowledge"; 3) All secondary teachers must help and give the students insights on reading preference and reading activities; 4) Future researchers should continue to research this area, particularly on the relationship of reading interest on Internet games and related matters, like, the impacts of Internet games on students' reading behavior.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: High school students -- Books and reading -- Philippines -- Tagaytay City; High school students -- Books and reading -- Philippines -- Silang (Cavite).; Reading interests -- Philippines -- Tagaytay City; Reading interests -- Philippines -- Silang (Cavite).